2019
DOI: 10.3390/agronomy9090491
|View full text |Cite
|
Sign up to set email alerts
|

Domesticating the Undomesticated for Global Food and Nutritional Security: Four Steps

Abstract: Ensuring the food and nutritional demand of the ever-growing human population is a major sustainability challenge for humanity in this Anthropocene. The cultivation of climate resilient, adaptive and underutilized wild crops along with modern crop varieties is proposed as an innovative strategy for managing future agricultural production under the changing environmental conditions. Such underutilized and neglected wild crops have been recently projected by the Food and Agricultural Organization of the United N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 56 publications
0
22
0
1
Order By: Relevance
“…It has been reported that only 12 crops contribute most to the current global food production, with only three of them (rice, wheat and maize) providing more than 50% of the world's calories [1][2][3]. Consequently, the Food and Agricultural Organization of the United Nations has predicted that the world is in need of about 70% more food to adequately feed the ever-growing population [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that only 12 crops contribute most to the current global food production, with only three of them (rice, wheat and maize) providing more than 50% of the world's calories [1][2][3]. Consequently, the Food and Agricultural Organization of the United Nations has predicted that the world is in need of about 70% more food to adequately feed the ever-growing population [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a detailed screening and exploration of hitherto wild and novel species from various agro-climatic regions of the world could help to mitigate the need. Although the crop breeding community is not yet unanimous on the importance of the crop neo-domestication concept, it is increasingly becoming popular in research on this topic that domesticating the undomesticated is an ideal method, which could aid in mitigating the global food insecurity challenges [1,5]. The method will not only promote the successful utilization of hitherto wild and non-domesticated food crops in dietary diversification programs, but also help with biodiversity conservation.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of multiple key domestication genes and scientific breakthroughs in introducing multiple genomic changes in plants simultaneously with CRISPR/Cas enables the domestication of wild species within a single plant generation (Schindele, Dorn, and Puchta 2019). De novo domestication can contribute to enhancing agrobiodiversity and dietary diversity with possible benefits for the environment and human nutrition (Singh et al 2019).…”
Section: New Domestication and Crop Diversitymentioning
confidence: 99%
“…Adoption of crop diversification practices in degraded lands can benefit restoration by increasing soil fertility, promoting sustainable agriculture and rural engagement. This involves the identification of wild varieties comparable in their nutritive profile to traditional crop plants and resilient enough to grow on degraded lands (Singh et al ). Secondly, development of suitable cropping strategies based on community and traditional tribal knowledge is required (Singh et al ; Priyadarshini & Abhilash ).…”
Section: Infusing Circularity Practices Within Lrmentioning
confidence: 99%